Direction, not destination: Institutional work practices in the face of field-level uncertainty. Issue 1 (February 2018) - Möllering, Guido; Müller-Seitz, Gordon
Abstract: Though field-level uncertainty represents a common challenge, research seldom addresses how institutional work that aims to influence institutional change occurs in the face of uncertainty. We study institutional work practices in a field beset with high uncertainty. Focusing on a field-configuring event in the semiconductor industry, we show how institutional work is possible through practices of dealing with uncertainty that do not eliminate the basic uncertainty but nevertheless configure the field and institutionalize a common direction without specifying a final destination. We find evidence of the open-endedness and collectiveness of institutional work and we contribute to the microfoundations of institutional theory conceptualizing a set of four practices of dealing with field-level uncertainty purposively but not purposefully, i.e., bootstrapping, roadmapping, leader-picking, and issue-bracketing. We highlight the reciprocal relationship between practices and uncertainty, focus on the coordination of institutionalization, and distinguish between events in fields marked by high versus low uncertainty.